2019
DOI: 10.15446/dyna.v86n211.79465
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broilers submitted to different intensities and duration of thermal stress

Abstract: The performance of broilers submitted to thermal discomfort in the first weeks of life may be impaired, since the thermoregulatory system of the bird is not fully developed. The objective of this study was to analyze the effects of different thermal challenges on the performance of broilers. Two hundred and forty broilers were submitted to different desired dry-bulb temperatures (tdb: 24, 27, 30 and 33°C) and stress duration (SD: 1, 2, 3 and 4 days) in the second week of life. Feed intake (FI), weight gain (WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study's findings indicated that the model successfully captured the dynamic interconnection between environmental conditions and broiler growth, highlighting the model's ability to accurately predict the future growth patterns of broilers based on the provided inputs. The authors of [32] demonstrated that their neural network model achieved satisfactory performance in predicting the feed conversion of broilers under heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings indicated that the model successfully captured the dynamic interconnection between environmental conditions and broiler growth, highlighting the model's ability to accurately predict the future growth patterns of broilers based on the provided inputs. The authors of [32] demonstrated that their neural network model achieved satisfactory performance in predicting the feed conversion of broilers under heat stress.…”
Section: Introductionmentioning
confidence: 99%